African-american vernacular english: a descriptive analysis of the comedy of Steve Harvey - Ruíz López, Diego Esteban (2019)
Stand-up comedy is one of the most representative forms of entertainment in the U.S. It plays a big role in the construction of identity of the various communities. It is the place where comedians can openly discuss about sensitive topics related to culture, such as racism, politics and religion. For minority groups such as African-Americans, it is a suitable environment to be honest and straightforward about social injustices. Humor is the channel through which comedians have been able to address these injustices and thus break the barrier of discomfort. African-Americans expose these topics using their language to affirm their identities, to promote pride for their community and to differentiate themselves from mainstream society. Based on this, the present study aims to describe and analyze the grammatical features as well as the rhetorical strategies that comedians such as Steve Harvey employ to build social identity. La comedia en vivo es una de las formas más representativas de entretenimiento en los Estados Unidos. Esta juega un papel importante en la construcción de la identidad de varias comunidades de dicha sociedad. Los comediantes pueden explayarse en este ambiente, al hablar sobre temas sensibles pertinentes a la cultura, tales como el racismo, la política y la religión. Para los grupos minoritarios como es el caso de los afroamericanos, este tipo de comedia resulta ser el ambiente propicio para hablar honesta y directamente acerca de las injusticias sociales. El humor es la herramienta con la que se ha podido traer a colación tales injusticias sin necesidad de sentirse incómodo. Los hablantes afroamericanos disponen de su lengua para hablar al respecto, y así lograr respaldar sus identidades, fomentar el orgullo en sus comunidades, y diferenciarse de la sociedad dominante. Dicho esto, el presente estudio tiene como objetivo describir y analizar las características gramaticales así como las estrategias retóricas que los comediantes como Steve Harvey emplean en la construcción de la identidad social.